Role of glia in optic nerve. (March 2021) - Yazdankhah, Meysam; Shang, Peng; Ghosh, Sayan; Hose, Stacey; Liu, Haitao; Weiss, Joseph; Fitting, Christopher S.; Bhutto, Imran A.; Zigler, J. Samuel; Qian, Jiang; Sahel, José-Alain; Sinha, Debasish; et al.
Abstract: Glial cells are critically important for maintenance of neuronal activity in the central nervous system (CNS), including the optic nerve (ON). However, the ON has several unique characteristics, such as an extremely high myelination level of retinal ganglion cell (RGC) axons throughout the length of the nerve (with virtually all fibers myelinated by 7 months of age in humans), lack of synapses and very narrow geometry. Moreover, the optic nerve head (ONH) – a region where the RGC axons exit the eye – represents an interesting area that is morphologically distinct in different species. In many cases of multiple sclerosis (demyelinating disease of the CNS) vision problems are the first manifestation of the disease, suggesting that RGCs and/or glia in the ON are more sensitive to pathological conditions than cells in other parts of the CNS. Here, we summarize current knowledge on glial organization and function in the ON, focusing on glial support of RGCs. We cover both well-established concepts on the important role of glial cells in ON health and new findings, including novel insights into mechanisms of remyelination, microglia/NG2 cell-cell interaction, astrocyte reactivity and the regulation of reactive astrogliosis by mitochondrial fragmentation in microglia. Article Highlights: The glial cells in the ON are critical to its functional integrity and homeostasis. The glial cell network maintains functional interactions among glia and the axons. The nuances of glial interactions in the ON may differ from other parts of the CNS.